Mentoring the Young Generation of Balongdowo in Making Hand-drawn Batik Through Local Culture-Based Educational STEAM Workshops - Sumartini Rahaju (Future Tecno-Science Publisher, 2025)
This program introduces an innovative approach to empower the youth of Balongdowo Village through the development of batik-making skills. This initiative seamlessly integrates a STEAM (Science, Technology, Engineering, Arts, and Mathematics) framework deeply rooted in local cultural education. By adopting the Asset-Based Community Development (ABCD) method, this program strategically identifies and optimizes community assets, including indigenous batik knowledge, local wisdom, and the creative potential of the younger generation. This approach addresses the crucial need to evolve cultural heritage practices, making them more engaging, relevant, and interdisciplinary for contemporary youth who thrive on creative, collaborative, and experiential learning. A series of structured and highly innovative STEAM educational workshops form the core of this program. Participants not only master traditional batik techniques but also delve into the scientific principles behind natural and synthetic dyes (Science), explore digital technologies for motif development (Technology), understand engineering principles for crafting simple batik tools (Engineering), cultivate aesthetic appreciation and artistic creation (Arts), and apply mathematical concepts for product design and scaling (Mathematics). This hands-on, interdisciplinary learning environment aims to foster a deeper understanding and appreciation of batik beyond mere craftsmanship. Expected outcomes include significant improvements in technical batik skills, a profound connection to local cultural heritage, and the cultivation of an entrepreneurial spirit driven by innovation. Ultimately, this program is designed as a sustainable model for culture-based education, ensuring the long-term preservation and dynamic revitalization of Balongdowo’s batik heritage through the active participation and ingenuity of its youth.